Preclinical characterization of substituted 6, 7-dihydro-[1, 2, 4]triazolo[4, 3-a]pyrazin-8(5H)-one P2X7 receptor antagonists. Issue 2 (15th January 2016) - Ameriks, Michael K.; Ao, Hong; Carruthers, Nicholas I.; Lord, Brian; Ravula, Suchitra; Rech, Jason C.; Savall, Brad M.; Wall, Jessica L.; Wang, Qi; Bhattacharya, Anindya; Letavic, Michael A.
Graphical abstract: Abstract: The synthesis, SAR, and preclinical characterization of a series of substituted 6, 7-dihydro[1, 2, 4]triazolo[4, 3]pyrazin-8(5 H )-one P2X7 receptor antagonists are described. Optimized leads from this series comprise some of the most potent human P2X7R antagonists reported to date (IC50 s < 1 nM). They also exhibit sufficient potency and oral bioavailability in rat to enable extensive in vivo profiling. Although many of the disclosed compounds are peripherally restricted, compound11d is brain penetrant and upon oral administration demonstrated dose-dependent target engagement in rat hippocampus as determined by ex vivo receptor occupancy with radiotracer5 (ED50  = 0.8 mg/kg).